Marketing Strategy for the Image of Private Educational Institutions in Increasing Student Interest - Arghanty S, Yenny; Khamidi, Amrozi; Amalia, Kaniati; Nursalim, Mochamad (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to analyze the image marketing strategy of private educational institutions in increasing student interest at SD Labschool Unesa. In the era of globalization and intense competition, educational institutions are required to implement effective marketing strategies to attract the interest of prospective students and maintain a positive image in the eyes of the public. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews, observation and documentation. The research results show that SD Labschool Unesa uses various marketing strategies, including the use of social media, community-based promotional activities, and improving the quality of educational services. The implementation of these strategies has succeeded in increasing the interest of new students, as well as strengthening the positive image of the institution among parents and the community. This research provides recommendations for other private educational institutions to optimize their marketing strategies in order to increase attractiveness and public trust.